Variation of the silicon optical parameters after rapid heat treatment - Anishchik, Victor M.; Harushka, Valiantzina A.; Pilipenka, Uladzimir A.; Ponariadov, Vladimir V.; Saladukha, Vitali A.; Omelchenko, Anna A. Omelchenko (Journal of the Belarusian State University. Physics, 2021)
The results of the effect of rapid heat treatment on the optical characteristics of a silicon wafer surface in the region of the G-point in the Brillouin zone are presented for different types of silicon wafers conductivity, their doping level, the covalent radii of dopants and the crystallographic orientation of the wafer surface. The absorption coefficient and refractive index of the initial 100 mm diameter samples KDB-12 <100>, KDB-10 <111>, KDB-0.005 <100> and KES-0.015 <100>, underwent standard chemical-mechanical polishing, was measured on a Uvisel 2 ellipsometer (Horiba Scientific, France) in the spectral range 0.6–6.0 eV (200–2100 nm) before and after rapid heat treatment. The incidence angle of the light beam was 70° relative to the sample plane. It is shown that the changes in the optical characteristics of the silicon surface in the spectral region of the location of the G-point in the Brillouin zone after rapid heat treatment is due to a decrease in the surface deformation potential due to solid-phase recrystallisation of the mechanically damaged layer. It has been established that carrying out the rapid heat treatment of silicon samples with a high boron concentration leads to a more significant decrease in the refractive index and absorption compared with silicon with a low boron concentration, due to an increase in the depletion of the silicon surface with boron as a result of diffusion processes at the silicon – silicon dioxide interface.